Q: solve by using PEMDAS: 8 x 2 +9 /3

A: This conversation has been flagged as incorrect. New answers have been added below ....

AngelInDisguise|Points 5049|

migzptz|Points 5430|

boopydoop1|Points 2229|

thederby|Points 1051|

skerifine|Points 0|

Erika08|Points 140|

Daarizky|Points 20|

Question

Asked 3/21/2012 11:16:47 AM

Updated 6/28/2014 2:56:14 PM

6 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by andrewpallarca [6/28/2014 2:50:33 PM]

Rating

3

4 + 3^2 / (6-4)

= 4 + 3^2 /2

= 4 + 9/2;

= 17/2 or 8 1/2

= 4 + 3^2 /2

= 4 + 9/2;

= 17/2 or 8 1/2

Added 6/28/2014 2:50:27 PM

This answer has been confirmed as correct and helpful.

3

8 x 2 +9 /3

= 16 + 3 = 19

= 16 + 3 = 19

Added 6/28/2014 2:51:11 PM

This answer has been confirmed as correct and helpful.

3

(5xy^4) (2x^2y) = 10x^3y^5

Added 6/28/2014 2:51:47 PM

This answer has been confirmed as correct and helpful.

3

4(x - 3) = 5(2x + 3);

4x - 12 = 10x + 15;

4x - 10x = 15 + 12;

-6x = 27;

x = -27/6 = -9/2

4x - 12 = 10x + 15;

4x - 10x = 15 + 12;

-6x = 27;

x = -27/6 = -9/2

Added 6/28/2014 2:53:13 PM

This answer has been confirmed as correct and helpful.

3

The degree of polynomial x^5 + x^3 - 5x^9 + 6x^2 is 9.

Added 6/28/2014 2:54:08 PM

This answer has been confirmed as correct and helpful.

3

x^0 is NOT equal to 0.

Anything that is raised to 0 is always equal to 1.

Anything that is raised to 0 is always equal to 1.

Added 6/28/2014 2:56:14 PM

This answer has been confirmed as correct and helpful.

solve for x: -3x =5User: sole for x: - 3x - 5 **Weegy:** C.) X **User:** multiply; (x + 5) (x- 3) **Weegy:** x > 2
**User:** factor complelety: 12x^2y +18xy^2 +6x **User:** evaluate: -9x^0 **Weegy:** The answer is 1. Anything to the power of 0 will equal 1. Try it on your calculator. **User:** Jocelyn has test scores of 80, 77, and 89 on her first tests in algebra. What must she score on her 4th test so she will have at least an 85 average? **Weegy:** (80+77+89+x)/4 = 85, (246+x)/4 = 85, 246+x = 340, x = 91. Jocelyn will need to score 91 on her 4th test to have at least an 85 average. **User:** Subtract: (x^2 + 2x -4) - (x^2- 5x + 2) (More)

Question

Expert Answered

Updated 7/16/2014 3:01:48 AM

5 Answers/Comments

- 3x - 5 < 10

- 3x < 10 + 5

- 3x < 15

x > -5

- 3x < 10 + 5

- 3x < 15

x > -5

Added 7/16/2014 2:57:47 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [7/16/2014 4:02:42 AM]

(x + 5) (x - 3) = x^2 - 3x + 5x - 15 = x^2 + 2x - 15

Added 7/16/2014 2:58:54 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [7/16/2014 4:02:55 AM]

12x^2y +18xy^2 + 6x = 6x(2xy + 3y^2 + 1)

Added 7/16/2014 3:00:24 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [7/16/2014 4:03:21 AM]

-9x^0 = -9

Added 7/16/2014 3:00:52 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [7/16/2014 4:03:34 AM]

(x^2 + 2x -4) - (x^2 - 5x + 2)

= x^2 + 2x -4 - x^2 + 5x - 2

= 7x - 6

= x^2 + 2x -4 - x^2 + 5x - 2

= 7x - 6

Added 7/16/2014 3:01:48 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [7/16/2014 4:03:51 AM]

27,004,941 questions answered

There are no comments.